Implementasi Teori Belajar Humanistik terhadap Pembelajaran Bahasa Indonesia di Kelas III A MI Islamiyah Malang - Mutik Nur Fadhilah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
Learning is a process of changing cognitive, affective and psychomotor aspects. A learning theory is needed that supports the learning process. One of them is humanistic learning theory which is integrated with Indonesian language learning. Where the background of this research intersects with crowds and in the development process which causes a lack of conducive learning process. One of the aims is to know the implementation and implications of humanistic learning theory on Indonesian language learning for grade III A students. The method used in this research method uses a qualitative approach with descriptive research type. The data used are obtained through the results of an overview of the research object and other data that is not in the form of numbers (primary and secondary data). Data collection was carried out through interviews, direct observation and documents. Data analysis techniques are obtained from the results of interviews, observations, documentation that has been compiled and a conclusion is drawn. Meanwhile, to determine the validity of a data through persistence of observation, triangulation and peer discussion. The implications of the research result can be seen from the aspects of teachers and students who are harmonious and the existence of associations that protect this interaction. This interaction creates a humanizing attitude towards humans in accordance with religious and ethical guidance that applies in society. And applying teaching methods must be adapted to the characteristics of each lesson and the suitability of the age level of students. So that it has implications for the attitude of changing polite speech according to the rules of the Indonesian language and in accordance with the values ​​of Insan Kamil.